Virtual monoenergetic images from spectral detector CT as a surrogate for conventional CT images: Unaltered attenuation characteristics with reduced image noise. Issue 117 (August 2019) - Große Hokamp, Nils; Gilkeson, R.; Jordan, M.K.; Laukamp, K.R.; Neuhaus, Victor-Frederick; Haneder, S.; Halliburton, S.S.; Gupta, A.
Abstract: Objective: This study aimed to identify the energy level of virtual monoenergetic images (VMI) that closest represents conventional images (CI) in order to demonstrate that these images provide improved image quality in terms of noise and Signal-to-noise ratio (SD/SNR) while attenuation values (HU) remain unaltered as compared to CI. Methods: 60 and 30 patients with contrast-enhanced (CE) and non-enhanced (NCE) spectral detector CT (SDCT) of the abdomen were included in this retrospective, IRB-approved study. CI and VMI of 66–74 keV as well as quantitative iodine maps were reconstructed (Q-IodMap). Two regions of interest were placed in each: pulmonary trunk, abdominal aorta, portal vein, liver, pancreas, renal cortex left/right, psoas muscle, (filled) bladder and subcutaneous fat. For each reconstruction, HU and SD were averaged. ΔHU and SNR (SNR = HU/SD) were calculated. Q-IodMap were considered as confounder for ΔHU. In addition, two radiologists compared VMI of 72 keV and CI in a forced-choice approach regarding image quality. Results: In NCE studies, no significant differences for any region was found. In CE studies, VMI72keV images showed lowest ΔHU (HUliver CI/VMI72keV : 104 ± 18/103 ± 17, p ≥ 0.05). Iodine containing voxels as indicated by Q-IodMap resulted in an over- and underestimation of attenuation in lower and higher VMI energies, respectively. Image noise was lower in VMI images (e.g. muscle: CI/ VMI72keV : 15.3 ± 3.3/12.3 ± 2.9 HU, p ≤ 0.05). Hence, SNR was significantly higher in VMI72keV compared to CI (e.g. liver 3.8 ± 0.6 vs 3.0 ± 0.8, p ≤ 0.05). In visual analysis, VMI72keV were preferred over CI at all times. Conclusions: VMI72keV show improved SD/SNR characteristics while the attenuation remains unaltered as compared to CI.